2015
DOI: 10.4040/jkan.2015.45.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia Screening Measures for Use in Nursing Homes: A Systematic Review

Abstract: Results show that GUSS and SSA are reliable and sensitive tools for screening dysphagia which nurses can use in nursing homes. Further research is needed to examine feasibility of screening with identified tools, and also, to establish effective and standardized protocols for these tools so they can be effectively incorporated into routine care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…A more formal approach may be used such as the bed side swallow assessments e.g., (TOR-BSST or GUSS [16,17] routinely used in stroke care. TOR-BSST has been validated in older patients [18]. A rapid screening questionnaire [19,20] must have reasonable specificity and sensitivity to trigger a referral to the speech and language therapy (pathology) department.…”
Section: Swallowing Problemsmentioning
confidence: 99%
“…A more formal approach may be used such as the bed side swallow assessments e.g., (TOR-BSST or GUSS [16,17] routinely used in stroke care. TOR-BSST has been validated in older patients [18]. A rapid screening questionnaire [19,20] must have reasonable specificity and sensitivity to trigger a referral to the speech and language therapy (pathology) department.…”
Section: Swallowing Problemsmentioning
confidence: 99%
“…Un reciente estudio de la Universidad de Seúl revisó 31 métodos de cribado (1992-2011) para elegir el óptimo basándose en: la calidad de la metodología de los estudios, propiedades de la medición de las herramientas utilizadas para la detección de disfagia y la aplicabilidad por enfermería. Concluyeron que los test GUSS (gugging swallowing screen) y SSA (standardized bedside swallowing assessment) son los que ofrecen mayor rigor científico y resultan aplicables en la práctica clínica diaria, sobre todo por enfermería (21).…”
Section: Evaluación De La Disfagia En El Paciente Con Ictusunclassified
“…In a study comparing SSA with summative clinical judgement of swallowing function, sensitivity was 0.97 and specificity 0.90, with positive and negative predictive values of 0.92 and 0.96 [9]. The protocol is considered the best non-instrumental screening tool for dysphagia after stroke in two systematic reviews [10, 11]. However, the methodological quality was questioned in another systematic review that suggested a possible risk of bias, partially due to the fact that summative clinical judgement was used as a reference test [12].…”
Section: Introductionmentioning
confidence: 99%